Religia w przestrzeni życia publicznego w regionach Europy Środkowej (Politeja, 2017)
Religion in the public life in the regions of Central Europe. Features of the Central European modelFor post‑communist states, which experienced programmative secularization of society, and are currently building civil society, the Western models of determining the place and role of religion in public sphere seem to be inadequate and simplistic. On the one hand, freedom of religion in this region symbolizes success of a new democratic order. On the other, the rapid pace of social, cultural and political changes causes dilemmas regarding the place of religion in public life, where religion is part of cultural, national and social identities. People are stretched between the freedom to be religious publicly, return to traditional religion and freedom of other choices. It therefore seems that, despite religious diversity and the presence of specific historical circumstances in individual countries, these societies share the perspective of determining the place of religion in the public sphere today, which is the basis of the specific features of religion in public life. The article presents an ovierview of observations and interpretations of characteristics of social practice to the presence of religion in the public sphere, which were distinquished on the basis of qualitative research conducted in Poland, Slovakia and Ukraine.